(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The research aims to analyze and determine the effect relationship between investors’ tendencies and the profitability of shares of companies in the financial markets. between the optimistic, the pessimistic, and the rational, which have a different effect on stock profits, or they do not have an effect, and this is related to the extent of the homogeneity of these beliefs, and then their impact on the prices and returns of traded shares. The importance of the study comes from the importance of the variables of the study, in which the independent variable of the study was the inclinations of stock investors, and the dependent one is the earnings per share. For these companies, the statistical tools of multiple regression, serial correlation, AR1 model, and the random walk model were used to analyze the relationship between variables. The results of this study show that there is a correlation relationship for some indicators of the independent variable with the dependent variable, and there is an effect relationship for some indicators of the independent variable with the dependent one, and that the Iraq Stock Exchange is not efficient, and if there is efficiency in some tests, it is in the weak form of efficiency. The most important recommendations of this study was the need to study the correlations and relationships between the indicators of the inclinations of ordinary stock investors and the efficiency of the financial market and follow up their impact and the reflection of this effect on the volume of trading, fluctuations in prices, returns, interest rates and other environmental and economic factors.